Food selectivity in Autism Spectrum Disorder: implications of eating, sensory and behavioural profile - Riccio, Maria Pia; Marino, Maria; Garotti, Raffaele; Tassiello, Annalisa; Maffettone, Valeria; Pezone, Mariangela; Bravaccio, Carmela (Frontiers in Psychiatry, 2025)
IntroductionTo characterise possible clinical associations between food selectivity, a typical aspect of Autism Spectrum Disorder (ASD), and certain commonly observed aspects of the phenotype: sensory abnormalities, challenging behaviour, autistic symptom intensity and Intellective Quotient.MethodsThe present is a retrospective observational study. Fifty-two ASD subjects were enrolled that underwent a comprehensive psychodiagnostic assessment including the Short Sensory Profile questionnaires (to assess sensory abnormalities), the Aberrant Behaviour Checklist (to assess challenging behaviour) and the Food Preference Inventory (to assess food selectivity). The possible association between food selectivity, the intensity of autistic symptoms and the presence or absence of associated Intellective Disability was also subsequently assessed. Any differences between female and male were also assessed.ResultsStatistically significant correlations were observed between tactile, gustatory and olfactory sensitivity and food selectivity. These modalities were also found to predict greater food selectivity on regression analysis. No significant correlations were observed between the behavioural profile, intellective quotient and intensity of autistic symptomatology with food selectivity. In addition no significant scores were observed on the basis of sex.DiscussionAs far as can be seen from the results, the food selectivity of ASD subjects appears to be underlain mainly by sensory abnormalities and does not correlate with other clinical aspects of ASD subjects. Despite this, a comprehensive assessment of the various phenotypical aspects is still of fundamental importance. Further studies that could lead to a progressive characterisation of the phenotypical aspects of ASD subjects in order to provide increasingly personalised treatment are therefore considered useful.